Abnormal Cortical Activation Patterns Among Chinese-Speaking Schizophrenia Patients During Category and Letter Verbal Fluency Tasks Revealed by Multi-Channel Functional Near-Infrared Spectroscopy - Li, Juan; Mu, Junlin; Shen, Chenyu; Yao, Guanqun; Feng, Kun; Zhang, Xiaoqian; Liu, Pozi (Frontiers in Psychiatry, 2021)
Functional near-infrared spectroscopy (fNIRS) has many advantages over other neuroimaging modalities for routine measurement of task-dependent cortical activation, but most fNIRS studies of schizophrenia have used letter fluency tasks (LFTs). Further, performances on category fluency tasks (CFTs) and LFTs may be distinct in Chinese patients due to the unique semantic features of Chinese written characters. To identify unique disease biomarkers measurable by fNIRS in Chinese schizophrenia patients, this study compared cortical oxygenated hemoglobin changes ([oxy-Hb]) during a Chinese LFT and CFT between patients and healthy controls. Inpatients of the Second Affiliated Hospital of Xinxiang Medical University were recruited from Match 2020 to July 2021. The Positive and Negative Symptom Scale (PANSS) was used to evaluate psychiatric symptoms. Dynamic changes in [oxy-Hb], an indicator of neural activity, were measured during CFT and LFT performance by 52-channel fNIRS. Forty-seven schizophrenia inpatients and twenty-nine healthy controls completed all tests. Schizophrenia patients showed significant cortical activation at 15 channels covering the left hemisphere and 17 channels over the right hemisphere during the CFT. During the LFT, activity was significantly increased at only six channels, all over the left hemisphere. In healthy controls, significant [oxy-Hb] increases were found at 24 channels over the left hemisphere and 19 channels over the right hemisphere during CFT. During the LFT, the HC group demonstrated significantly larger [oxy-Hb] increases at 7 channels over the left hemisphere compared to patients. During the CFT, schizophrenia patients exhibited reduced activation versus controls in regions of the right posterior cingulate gyrus (PoCG), bilateral supramarginal gyrus (SMG), bilateral inferior frontal gyrus, and left medial frontal gyrus (MFG). During the LFT, deactivation in patients was observed in the right PoCG, left MFG, right SMG, and left superior fontal gyrus. The change of [oxy-Hb] in right PoCG during CFT was positively correlated with PANSS-positive score, while [oxy-Hb] of left inferior frontal gyrus and bilateral middle frontal gyrus during the LFT was negatively associated with PANSS-negative score. Left lateralization during CFT was reduced among schizophrenia patients and may be related to the semantic deficit. The Chinese-CFT could be a more sensitive indicator of frontal-temporal dysfunction in schizophrenia.